Between trust and control: Teachers' assessment conceptualisations within programmatic assessment - Schut, Suzanne (Med Educ, 2020)
OBJECTIVES: Programmatic assessment attempts to facilitate learning through individual assessments designed to be of low‐stakes and used only for high‐stake decisions when aggregated. In practice, low‐stake assessments have yet to reach their potential as catalysts for learning. We explored how teachers conceptualise assessments within programmatic assessment and how they engage with learners in assessment relationships. METHODS: We used a constructivist grounded theory approach to explore teachers' assessment conceptualisations and assessment relationships in the context of programmatic assessment. We conducted 23 semi‐structured interviews at two different graduate‐entry medical training programmes following a purposeful sampling approach. Data collection and analysis were conducted iteratively until we reached theoretical sufficiency. We identified themes using a process of constant comparison. RESULTS: Results showed that teachers conceptualise low‐stake assessments in three different ways: to stimulate and facilitate learning; to prepare learners for the next step, and to use as feedback to gauge the teacher's own effectiveness. Teachers intended to engage in and preserve safe, yet professional and productive working relationships with learners to enable assessment for learning when securing high‐quality performance and achievement of standards. When teachers' assessment conceptualisations were more focused on accounting conceptions, this risked creating tension in the teacher‐learner assessment relationship. Teachers struggled between taking control and allowing learners' independence. CONCLUSIONS: Teachers believe programmatic assessment can have a positive impact on both teaching and student learning. However, teachers' conceptualisations of low‐stake assessments are not focused solely on learning and also involve stakes for teachers. Sampling across different assessments and the introduction of progress committees were identified as important design features to support teachers and preserve the benefits of prolonged engagement in assessment relationships. These insights contribute to the design of effective implementations of programmatic assessment within the medical education context.